Lightweight flexible composite material with superior electromagnetic interference shielding and impact resistance properties - Wen, Haolijie; Ma, Jingtao; Jiang, Yang; Xiong, Ziming; Zhang, Zhongwei; Yu, Kejing (Composites communications, 2024)
Electromagnetic interference (EMI) has been shown to be detrimental to human health and hinders the normal operation of precision instruments. In addition, mechanical impact is ubiquitous in daily life, which has increased the demand for advanced protective materials. However, existing protective materials are not very effective in defending against these complex threats, and realizing a protective material with the dual function of EMI shielding and high impact resistance still remains a challenge. Here, we used aramid nanofibers (ANF) to assist MXene in constructing an aerogel skeleton in a spacer fabric (SF) and composite it with a shear stiffening gel (SSG) polymer. This lightweight and flexible SF/ANF/MXene/SSG (SAMS) composite enables the coupling protection of EMI/impact. The composite shows excellent EMI shielding capability with a shielding effectiveness of 65.5 dB, and a stable EMI shielding performance (49.7 dB, 44.5 dB) even after being subject to continuous hammering or violent impact. In addition, owing to the large number of micropores inside the SAMS and the good absorption of energy by the SSG, the SAMS effectively attenuates 44.8%–64.7% of the impact force, with excellent energy dissipation capability (>90%). Compared with commercial cushioning materials represented by silicone rubber and PU foam, SAMS has 270% and 46% higher specific energy absorption, respectively, while having a density of only 0.389 g/cm3. SAMS has a low density and a high specific energy absorption capacity, which is usually contradictory in traditional engineering materials. It is expected to be a reasonable substitute to commercial buffer materials. [Display omitted] •A multifunctional protective material (SAMS) was prepared by a simple method.•The SAMS composite integrates EMI shielding and impact resistance properties.•The porous structure and SSG synergistically enhance energy absorption.•The SAMS composite sees stellar prospects for its application in personal protection and electronic equipment.